Hubungan Asupan Lemak Dan Rasio Lingkar Pinggang Panggul(Rlpp) Dengan Kadar Low Density Lipoprotein (Ldl) Pada Wanita Menopause Di Posyandu Ngudi Waluyo Surakarta - Rahmawati, Nesti (2016)
Introduction: Beside hormonal factors, high intake of fat and waist to hip ratio (WHR) are predicted as risk factorstothe increasing of LDL levels in menopause women. Objective: The aim of the present study was to assess association fat intake and WHR with LDL levels in menopause women. Methods: A cross sectional study was conducted in a simple random sample of 33 menopause women aged 45-65 years in Posyandu Ngudi Waluyo Surakarta. An average of three 24-hour dietary recalls of each woman was analysed using Nutrysurvey to obtain fat intake. WHR and LDL concentration each respondent were undertake. Results: Seventeen (51.5%) participants had high intake of fat, 26 (78.8%) participants with WHR more than 0,85 cm and 15 (45%) had LDL concetration above 150 mg/dL. There was no relationship between fat intake and LDL concentration (p=0.139) as well as WHR and LDL levels (p=0.67). Conclusion: Both fat intake and WHR appeared not tobe the risk factor to the increasing of LDL level in menopause women at the Posyandu Ngudi Waluyo Surakarta. Keywords: Fat Intake, LDL Level, Menopause, Waist to Hip Ratio Bibliography: 43 (1995-2015)